PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN SIKAP ILMIAH DAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA BIOLOGI KELAS VII4 DI SMP NEGERI 2 TAMBANG T.P 2015/2016 - Fat Elissa; Yuslim Fauziah; Arnentis ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The aim of this research was to improve scientific attitude and biology learning result of students class VII4 at SMPN 2 Tambang with the application of think pair share model academic year 2015/2016. This research was conducted at SMPN 2 Tambang class VII4 on Maret until April 2016. This research was a classroom action research and collaborated with teacher of SMPN 2 Tambang. Subject of this research was student class VII4 that consist of 20 student (11 girls and 9 boys). The parameters of this research were scientific attitude and learning result. Scientific attitude consist of curiosity, collaboration, disiplin, responsibility and percayadiri. Learning result consist of reserve capacity and student thoroughtness. Data analysis consist of scientific attitude and students learning result. The result showed that the mean score of scientific attitude on 1 st cycle was 69,25%(kurang) and increased on 2nd cycle with the mean score was 89,75%(good). For reserve capacity, the mean score on 1 st cycle was 70,5%(kurang) and increased on 2 nd cycle with the mean score was 83%(good). For students thoroughness individually, the mean score was 80%(thorough) on 1 st cycle and 100%(thorough) on 2 nd cycle. Based on the result, it can be conclude that the application of think pair share model could improve scientific attitude and biology learning result of student class VII4 at SMPN 2 Tambang academic year 2015/2016.Key words : Improve scientific attitude, think pair share model, biology learning result